Investigation of zinc oxide thin film by spectroscopic ellipsometry - Dinh, Nguyen Nam; Trung, Tran Quang; Binh, Le Khac; Khoa, Nguyen Dang; Mai Thuan, Vo Thi (VNU Journal of Science: Mathematics - Physics; Vol 24 No 1, 2008)
Abstract